Design of Compact, Low-cost Electrochemical Electronic Reader (Potentiostat) for Chemical Compound Analysis - Harimurti, Suksmandhira; Gamalyn, Irene Maria; Johan, Tengku Abdurrazak; Septian, M. Rivaldi Ali; Anshori, Isa; Estananto, Estananto (IAES Indonesian Section, 2025)
The development of low-cost electrochemical electronic reader (potentiostat) has been vastly growing recently since it could serve as a rapid chemical compound detection. Nevertheless, the realization of a low-cost potentiostat, having a compact size and providing multi-feature, is challenging. Here, a compact, low-cost potentiostat, supporting multi electrochemical methods was demonstrated. The total dimension was (10.8 x 4.6 x 3.5) cm3 with the weight of only 75.6 g. By using 16-bit analog-to-digital converter (ADC) and 12-bit digital-to-analog converter (DAC) components, the potentiostat facilitated a current input range of ±580 µA with a resolution of 23.5 nA and a voltage sweep range of ±1.5 V with a resolution of 800 µV. For the electrochemical measurement, it supported cyclic voltammetry (CV) and differential pulse voltammetry (DPV) methods. Furthermore, in comparison with a commercial potentiostat (Sensit Smart), the potentiostat showcased a good accuracy performance. In detail, the average relative accuracy of the CV method test was 91% and 95% for the anodic (Ianodic) and cathodic peak currents (Icathodic), respectively. For DPV method, the lowest relative accuracy of the peak current (Ipeak) was still 83%. These results demonstrated that our potentiostat could promisingly be utilized for chemical compound detection in low-cost setting or rural areas.